Efficacy of water-based skin decontamination of occupational chemicals using in vitro human skin models: a systematic review. (3rd October 2021) - Chiang, Chavy; Kashetsky, Nadia; Feschuk, Aileen; Burli, Anuk; Law, Rebecca; Maibach, Howard
ABSTRACT: Percutaneous absorption of chemicals is a potential route of topical and systemic toxicity. Skin decontamination interrupts this process by removing contaminants from the skin surface. Decontamination using water-only or soap and water solutions is the current gold standard despite limited efficacy data. A summary of studies evaluating their efficacy in decontaminating occupational contaminants from in vitro human skin models is presented. Embase, MEDLINE, PubMed, Web of Science, and Google Scholar were searched for relevant articles and data extracted from 15 investigations that reported on 21 occupational contaminants, which were further classified as industrial chemicals, drugs, or pesticides. Water-only decontamination yielded no response in 4.3% ( n = 6/140) and partial decontamination in 95.7% ( n = 134/140) of skin samples. Soap and water decontamination yielded complete decontamination in 4.9% ( n = 13/264) and partial decontamination in 95.1% ( n = 251/264) of skin samples. Four studies (26.7%, n = 4/15) reported increased penetration rates or skin concentration of contaminants following decontamination, demonstrating a "wash-in" effect. Varying study methodologies hinder our ability to compare data and determine when water alone or soap and water are best used. International harmonized efficacy protocol might enhance our decontamination understanding and enable a more customized approach to decontamination clinical practice and research.